Epidemiology of meningitis due to Haemophilus influenzae type b in children in Bulgaria: a prospective, population-based surveillance study - Kojouharova Mira; Gatcheva Nina; Setchanova Lena; Robertson Susan E.; Wenger Jay D. (The World Health Organization, 2002)
OBJECTIVE: To assess the incidence of meningitis caused by Haemophilus influenzae type b (Hib) among children in Bulgaria and to provide evidence for an informed decision on the use of Hib vaccines in Bulgaria. METHODS: From 1 July 1997 to 31 December 1999, active surveillance for meningitis was conducted in six regions. For children with suspected meningitis, a cerebrospinal fluid (CSF) specimen was sent for cytology, chemistry, latex agglutination testing, culture and sensitivity. FINDINGS: During the 2.5-year study period, surveillance was conducted among 138 249 children aged <5 years - a sample representing 40% of all Bulgarian children in this age group. Overall, 285 children with suspected meningitis were identified. In eight children, clinical symptoms of meningitis resolved rapidly before a CSF specimen could be obtained. Of the remaining 277 children, 121 (44%) were classified as having probable bacterial meningitis on the basis of a CSF examination. An organism was identified for 88 (73%) of the 121 cases with probable bacterial meningitis. There were 21 cases of Hib, giving a mean annual incidence of 6.1 Hib meningitis cases per 100 000 children <5 years; the case-fatality rate was 10%. Nearly 60% of Hib isolates were resistant to one or more antibiotics, but they were not resistant to third-generation cephalosporins. CONCLUSION: On the basis of these findings, Hib conjugate vaccines have been included in the list of vaccines recommended for children by the Bulgarian Ministry of Health. The recommended initial treatment for paediatric bacterial meningitis has been changed to third-generation cephalosporins.